PENGARUH MEDIA KOTAK ANGKA TERHADAP HASILBELAJAR SISWA PADA MATERI PERKALIAN DALAM PEMBELAJARAN MATEMATIKA KELAS III UPTD SD NEGERI 30 BARRU - Annisa; Ernawati; Andi Alim Syahri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The study aims to determine the effect of number box media on student learning outcomes on multiplication material in mathematics learning for grade III UPTD SD NEGERI 30 BARRU. The problem raised in this study is the low student learning outcomes, especially on multiplication material, which is caused by the lack of interesting and interactive learning media for that, learning media innovation is needed that can improve student understanding and learning motivation. The type of research used is a pre-experimental with a One Group Pretest-Posttest design. This research was conducted at UPTD SD NEGERI 30 BARRU with research subjects all grade III students. Data collection techniques used observation, tests (pre-test and post-test), and documentation. Data analysis used descriptive and inferential statistics with the N-Gain test and hypothesis testing (t-test). The results showed that there was an increase in learning outcomes after using number box media. The average pre-test score of 47.50 increased to 86.25 in the post-test. The N-Gain value of 0.74 is considered high, indicating that the number box media has a significant effect on improving student learning outcomes in mathematics. Therefore, the number box media can be used as an effective alternative learning medium to improve student learning outcomes, particularly in multiplication.